2010
DOI: 10.1128/iai.00808-09
|View full text |Cite
|
Sign up to set email alerts
|

Treponema denticolaSuppresses Expression of Human β-Defensin-3 in Gingival Epithelial Cells through Inhibition of the Toll-Like Receptor 2 Axis

Abstract: We reported previously that Treponema denticola, one of the periodontal pathogens, suppresses the expression of human ␤-defensins (HBDs) in human gingival epithelial cells. To identify the mechanisms involved in this suppression, immortalized and normal human gingival epithelial cells were infected with live or heat-killed T. denticola for 24 h, and then the expression of HBDs was examined by real-time RT-PCR. Live T. denticola suppressed the expression of HBD-3 substantially and also suppressed the expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 30 publications
1
35
0
Order By: Relevance
“…There have been only a few reports with respect to interruption of TLR function by bacteria; Brucella melitensis and uropathogenic E. coli possess genes encoding homologs of the TIR domain, with interacts with MyD88 and interrupts TLR signaling (9). Live but not heat-killed Treponema denticola suppress expression of human ␤-defensin 3 from gingival epithelial cells via inhibition of TLR2 signaling (27). The former interrupts the intracellular signaling pathway of TLRs by binding to their intracellular domain, but the mechanism of the latter action has not been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…There have been only a few reports with respect to interruption of TLR function by bacteria; Brucella melitensis and uropathogenic E. coli possess genes encoding homologs of the TIR domain, with interacts with MyD88 and interrupts TLR signaling (9). Live but not heat-killed Treponema denticola suppress expression of human ␤-defensin 3 from gingival epithelial cells via inhibition of TLR2 signaling (27). The former interrupts the intracellular signaling pathway of TLRs by binding to their intracellular domain, but the mechanism of the latter action has not been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…T. denticola can evade aspects of the innate immune defense by preventing efficient binding of antimicrobial peptides, such as β-defensins, that are produced by epithelial cells, and by inducing rapid efflux of some host defense peptides which enter the cytoplasm (Brissette and Lukehart, 2007). Recently, T. denticola has also been shown to suppress the production of β-defensin 3 by human gingival epithelial cells (Shin et al, 2010).…”
Section: Immunomodulation and Immuno-evasionmentioning
confidence: 99%
“…A study from another group reported mice given oral doses of P. gingivalis showed alveolar bone loss, but in PAR-2 deficient mice the amount of bone loss was significantly less, indicating PAR-2 may have a role in the inflammatory response against P. gingivalis (Holzhausen, Spolidorio et al 2006). In addition, a recent study revealed that the expression of hBD-3 in response to another periodontal pathogen T. denticola is regulated via TLR2 (Shin, Kim et al 2010). All these studies strongly suggest gingival epithelia are able to sense microbes, distinguish between commensal and periopathogenic bacteria, and regulate the appropriate responses for inflammation via regulation of AMPs.…”
Section: Beta-defensinsmentioning
confidence: 97%